1999
DOI: 10.1590/s0100-879x1999001200018
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effect of antidopaminergic drugs or estrogen on male Wistar rat lactotrophs and somatotrophs

Abstract: The aim of the present study was to evaluate the effect of antidopaminergic agents on the somatotrophs in the presence of hyperprolactinemia. Adult male Wistar rats were divided into 6 groups: a control group and five groups chronically treated (60 days) with haloperidol, fluphenazine, sulpiride, metoclopramide or estrogen. Somatotrophs and lactotrophs were identified by immunohistochemistry and the data are reported as percent of total anterior pituitary cells counted. The drugs significantly increased the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The percentage of lactotrophs found in the control group was within the range previously reported for adult male Wistar rats, i.e., 10.5% (26), 15% (27), 21.7% (28), and 26% (29).…”
Section: Discussionsupporting
confidence: 87%
“…The percentage of lactotrophs found in the control group was within the range previously reported for adult male Wistar rats, i.e., 10.5% (26), 15% (27), 21.7% (28), and 26% (29).…”
Section: Discussionsupporting
confidence: 87%
“…Immunohistochemistry, however, may reveal increased or decreased lactotroph immunoreactivity for prolactin (Spritzer et al, 1996;Oliveira et al, 1999). In estrogen-stimulated rats treated with bromocriptine, a decreased labeling index for the proliferating cell nuclear antigen and increased apoptotic nuclei correlated with hypoprolactinemia, indicating reduced cellular proliferation and increased cell death (Yonezawa et al, 1997).…”
Section: Effect On Pituitary Weight or Histomorphologymentioning
confidence: 99%
“…It has been demonstrated that estrogens act on the biosynthesis and secretion of all hormones of the anterior pituitary and stimulate the proliferation of lactotropes and gonadotropes [1, 2, 3, 4, 5, 6, 7, 8]. The physiological effects of estrogen on the pituitary gland, including cellular proliferation and hormone synthesis regulation, are mediated by the nuclear estrogen receptor (ER), which exhibits two separate but related forms: ERα and ERβ, with different patterns of expression in tissues and cells.…”
Section: Introductionmentioning
confidence: 99%